A Systematic review of the literature on learning and teaching of wave-particle duality - Laura Buteler; Luciano Ferrufino; Nicolas Velasco; Nicolás Gandolfo; Dayana Alvarez (Revista Brasileira de Ensino de Física)
Fundamental notions of quantum physics are included in introductory university curricula, in physics teacher training, and even in secondary education, both in Argentina and in various other countries worldwide. Among these fundamental concepts is wave-particle duality (WPD), a key concept and a gateway to the quantum world. This paper presents a critical review of the literature on WPD in specialized journals on physics education and science education at the local, regional, and international context, aiming to gather the most relevant findings regarding its teaching and learning. Preliminary results indicate that these findings can be categorized based on their primary purpose into four categories: Teaching WPD, Learning WPD, Historical and Epistemological Reflections on WPD and Reviews on the Teaching and Learning of Quantum Physics (including WPD).